1937 Elections: The Congress and AKALI PARTY (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
The first and the second elections to the provincial legislature were held in British India under the Government of India Act of 1935 .The situation was different in the Punjab from rest of India as here three were three rather than two communities to share powers.[1] The communal problem, being three dimensional, in the Punjab, was very complicated and had led to the growth of a large number of communal parties in this province than elsewhere.[2] It was a Muslim majority province with Muslims as per the Census Report of 1931 constituting 56.54% of the population,[3] The Hindus were 27.8 per cent and the Sikhs were 13.2 per cent. It was the only province where the majority community had been granted,[4] the right of separate representation. Under the Government of India Act of 1935, the elections in the Punjab were held in the beginning of 1937. The Unionists, Congress, Akalis and the Muslim League were the major political parties contesting elections.